The Influence of Leadership, Organizational Learning, Job Characteristics, and Work Motivation on Employee Performance at Bhayangkara Hospital Banjarmasin - Melania; Kadir, Abdul; Jayen, Fredy; Amrulloh, Rifqi; Aranza, Donny (Archives of Business Research, 2023)
This study aims to determine and analyze the simultaneous and partial influences of leadership, organizational learning, job characteristics, and work motivation on employee performance at Bhayangkara Hospital in Banjarmasin. The respondents of this study are employees at Bhayangkara Hospital, with a total of 73 respondents determined using the Slovin formula. The population used in this study consists of all medical and non-medical employees of Bhayangkara Banjarmasin Hospital, totaling 266 individuals, who serve as respondents. Since the population consists of more than 100 employees, the sampling in this study was conducted by randomly selecting a sample from all employees of Bhayangkara Banjarmasin Hospital.The research instrument used in this study is a questionnaire, which underwent validity and reliability testing. The data were analyzed using multiple linear regression analysis, while also fulfilling the assumptions of classical tests. The results of the study indicate that leadership, organizational learning, job characteristics, and work motivation have both simultaneous and partial influences on employee performance at Bhayangkara Hospital in Banjarmasin.